"When We Do Evict Them, It's a Last Resort": Eviction Prevention in Social and Affordable Housing. Issue 3 (4th May 2022) - Collins, Damian; de Vos, Esther; Evans, Joshua; Severson Mason, Meryn; Anderson-Baron, Jalene; Cruickshank, Victoria; McDowell, Kenna
ABSTRACT: Evictions are a common contributing factor to homelessness and are experienced overwhelmingly by vulnerable populations, including low-income households, single parents, and minority groups. At the same time, social and affordable housing providers serve increasingly vulnerable populations. Although all evictions are potentially problematic, those that occur in social and affordable housing can carry particularly severe consequences. Little research exists on evictions in social and affordable housing, and there is even less on eviction prevention practices in this sector. This project seeks to fill this research gap by exploring emerging eviction prevention practices in social and affordable housing in Edmonton, Alberta, Canada. Our findings show that evictions are a complicated process for both tenants and housing providers, and most commonly occur because of rent arrears. Housing providers try to prevent evictions, and toward this end, they have adopted four broad eviction prevention practices, centered on financial management, regular communication with tenants, provision of tenant supports, and community development. However, housing providers are often constrained in their ability to prevent evictions, in particular by human resource and financial limitations. These challenges lead to complex negotiations between housing providers' social mandates to provide affordable housing to vulnerable households and their regulatory and operational environments.